Child Marriage: A Discussion Paper (Bangladesh Journal of Bioethics, 2015)
Child marriage is still a massive problem in many developing countries. The issue is more concentrated in countries of Sub Saharan Africa and South Asia. This paper, through literature review attempts to assess the situation, the consequences, various programmes and recommendations on the reduction of child marriage. In this article it is reinforced that, consequences of child marriage put the girls at risk of early pregnancies with life-threatening conditions. This paper suggests that each country should set up its own mid-term and long-term goals to bring about significant reduction in child marriages.